PARTISIPASI PUBLIK DALAM REVISI UNDANG-UNDANG TENTANG KOMISI PEMBERANTASAN KORUPSI (KPK) - Hafifurrahman; Azhar Kasim (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
In accordance with public demands that mandate public participation in decision-making involving the public interest within the framework of Good Governance, it requires the Government to consider ideas and suggestions as well as input from the public. Therefore, public participation is an element of the ideal governance process in a democratic country like Indonesia. Therefore, public participation must get our attention as a counterweight and filter of decisions and policies to be taken by the Government. For this reason, we must ensure that the results of public participation can be accommodated and accommodated by the government, especially the legislature that is authorized to draft laws as guidelines for administering government in Indonesia. A good law will produce a good order of life. On the other hand, if the product of the law is bad, then the order of life in the state will also be bad. In Indonesia, the institutions that have the authority to make laws are the People's Representative Council (DPR) and the Regional Representative Council (DPD) in a system called bicameral. However, recently, this legislative body which consists of two chambers has revised the Law governing an Independent Institution, namely the Corruption Eradication Commission (KPK). However, the formulation and establishment of this law was deemed not transparent and full of the interests of the political elite to castrate the KPK's authority. Therefore, this paper will discuss how public participation is in revising the Law on the KPK.